DYSTOPIAN YOUTH IN CHETAN BHAGAT’S FIVE POINT SOMEONE (International Journal of Food and Nutritional Sciences, 2022)
The present paper entitled “Dystopian Youth” brings out the life style and plight of contemporary tech-savvy youth with positive resolutions as presented by Chetan Bhagat in his fiction Five Point Someone. The present postmodern age witnesses grey revolution born out of ICT (Information and Communication Technology) developments. The new life style of today’s youth fostered by the excessive dependency on technology is filled with technoculture. Today’s youth has their unique tech-savvy culture which is often filled with dystopian attitude that reveals the materialized life and insensible attitude of contemporary youth to whom life is nothing but just a global market. Chetan Bhagat, a social critic presents how today’s youth used to live with technology and love synthetic mutant things. He never hesitates to leave plastic and carbon foot prints to futurity which would be full of dystopian life style and virtual reality. Bhagat’s unique voice for the sensibility of youth, with their aspirations, dreams, love, pain, exam fear, pressure of assignments, friendship and so on are more natural. The paper aims to focus on the highly potential youth of today who could not find time to stand and stare. They are ready to lose life itself in their strive to live comfortable materialized sophisticated and decent life. The paper analyses the contemporary dystopian youth who are forced to live with technoculture in today’s mechanized societies.